SISTEM INFORMASI QUICK RESPONSE CODE (QR CODE) SEDERHANA UNTUK MENGOPTIMALKAN INVENTARISASI PEMINJAMAN DAN PENGGUNAAN ALAT-ALAT LABORATORIUM DI JURUSAN ILMU TANAH, UNIVERSITAS MATARAM - Dori Kusuma Jaya; Lolita Endang Susilowati; Hendra R. Akhdiyat (Universitas Mataram, 2023)
Digital-based laboratory inventory management has begun to be implemented in various universities today. The Laboratory of Soil Science, University of Mataram needs to apply this method to improve the quality of practicum and research services. The borrowing and use of laboratory equipment by conventional methods make it difficult for laboratory staff to store and secure data properly. This community service aims to optimize the conventional method with a method based on the Quick Response Code (QR Code). The design of the QR Code was carried out online which was then attached to each tool and then tested and socialized to users. This program was carried out for 2 months from August to September 2022. The output of this service is the design of a simple QR Code-based information system that can simplify the process of borrowing tools and make them easier to use. The results of implementing the QR Code show that storing data is more well-organized and safe and also makes it easier for beginner users to use the laboratory equipment with the operational procedure and video tutorials provided.